2014
DOI: 10.1155/2014/620389
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Research on Hydraulically Generated Vibration and Noise of a Centrifugal Pump Volute with Impeller Outlet Width Variation

Abstract: The impeller outlet width of centrifugal pumps is of significant importance for numbers of effects. In the paper, these effects including the performance, pressure pulsations, hydraulically generated vibration, and noise level are investigated. For the purpose, two approaches were used to predict the vibration and sound radiation of the volute under fluid excitation force. One approach is the combined CFD/FEM analysis for structure vibration, and then the structure response obtained from the FEM analysis is tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Impeller outlet width [112,113] • The decrease of impeller outlet width weakens the pressure fluctuations intensity and leads to the decrease of vibration and noise.…”
Section: Pump Structures References Key Findingsmentioning
confidence: 99%
“…Impeller outlet width [112,113] • The decrease of impeller outlet width weakens the pressure fluctuations intensity and leads to the decrease of vibration and noise.…”
Section: Pump Structures References Key Findingsmentioning
confidence: 99%
“…The pump is expected to run at the high efficiency zone under the mean head of the pump station, and the designed flow rate is to be met under the design head and under the maximum head the safety and stable operation must be unconditionally satisfied. And better cavitation characteristics are also considered during the pump selection and their performance comparison, as discussed in [4][5][6].…”
Section: The Requirement Of Pump Selectionmentioning
confidence: 99%
“…Zhang et al 11 obtained vibration signals at different flow rate of a slope volute pump by experiment, and compared with the vibration characteristics of the traditional spiral volute pump. Liu et al 12 adopted CFD/FEM analysis method and CFD/ FEM/BEM coupling method to detect the sound radiation and vibration of the volute under fluid excitation force. Results showed that the sound pressure effect on the structure of the centrifugal pump was not significant.…”
Section: Introductionmentioning
confidence: 99%